Export determinants and its long-run relationship of Malaysia's major export sectors - Lee, Pit Yean (2005)
Many empirical studies have tried to establish the causal link between export expansion and economic growth, due to the view that structural changes in a nation will alter the sources of growth, which in turn will affect the export-oriented strategy that can be used. The main purpose of this study is to explore the long run convergence of Malaysia's three main export sectors; namely agriculture, manufacturing and services sector, and the determinants of export expansion, by using the cointegration framework. Using annual data for 1960-2002, this paper explores a model in which growth of exports is determined by a combination of human capital, research and development adoption, labor productivity, labor wage rate, real effective exchange rate, imports of capital and intermediate goods as well as gross domestic product or GDP. The results show that the growth of exports of each sector and their respective export determinants were cointegrated, implying that there exists a steady-state relationship between the series. The results of the vector error-correction model or VECM also indicate that in the long run, the hypothesis that GDP-driven exports and imports Granger-causes growth of exports cannot be rejected at the 5% significance level, as for the case of agriculture and manufacturing sector. For the services sector, the hypothesis that productivity-led export and human capital Granger-cause services export also cannot be rejected, indicating a long run relationship between growth of exports and labor productivity as well as development of human capital. The weakening support for export-led growth after Malaysia shifted to an export-oriented development strategy is associated with structural changes associated with industrialization.